Relationship between DNA methylation and expression of plant transgenes in the system Nicotiana tabacum - Crhák Khaitová, Lucie, 1983- (2007)
English annotation This work was focused on the study of the in trans silencing capacity of the trigger locus 271. This locus has been shown to induce inactivation and methylation of the 35S and 19S viral promoters in plant transgenic systems. Locus 271 was combined with the transgenic acceptor loci carrying the bacterial neomycin phosphotransferase II reporter gene driven by the 35S promoter in tobacco hybrid plants. Two genomic organizations of the acceptor loci can be recognized: (i) a single T-DNA insertion within the locus 2 actively expressing the reporter transgene (ii) inverted repeat configuration of two T-DNA copies residing locus 1. The nptII genes in this locus are posttranscriptionally silenced (PTGS). In 271/1 and 271/2 hybrids, we determined expression of the nptII reporter transgene. In parallel, methylation of promoter sequences was analyzed. The silencer locus 271 induced significant reduction of the nptII expression in both locus 1 and locus 2. However, wh.